Audio beam : a new type of loudspeaker design - Gan, Woon Seng (2008)
Audio Beam is a revolutionary way of projecting audio signals in a highly directional manner to the listener. Instead of using conventional large loudspeaker arrays for projecting a narrow sound beam to the listener, this new technique creates the same narrow beam by amplitude-modulating the audio signal with a finite amplitude ultrasonic carrier wave and then transmitting the resultant signal from an array of ultrasonic transducers across the air to the listener. As a result, an audio signal is automatically produced by the self-demodulation effect of the amplitude-modulated sound wave in the air, without the aid of any hearing device. With this nonlinear interaction, we develop a new type of loudspeaker capable of controlling the direction of the transmitted audio signal.